LITERATURE REVIEW IRREGULAR MENSTRUAL CYCLE BASED ON BMI AND BODY FAT PERCENTAGE - Nurul Hikma; Zakiyatul Faizah; Rize Budi Amalia (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: The menstrual cycle can be said to be normal if the interval is between 21-35 days. The prevalence rates associated with menstrual cycle disorders were found in the range of 15.8-89.5. Nutritional status is one of the factors that cause menstrual cycle disorders, where nutritional status can be determined using body mass index and measuring the percentage of fat in the body. The purpose of this study was to determine the relationship between nutritional status and the menstrual cycle using the literature review method. The formulation of the problem in this research is determined by PICO, namely: